PROTECTION GUARANTEES FOR WHISTLEBLOWERS REGARDING INFORMATION ON NARCOTICS ABUSE BY THE COMMUNITY - Riana Putra Intaran, Galih; Bagiastra, I Nyoman (Penerbit Lafadz Jaya, 2023)
Purpose of the article This is to provide an overview of drug abuse regulations in Indonesia and explain protection for whistleblowers related to providing information on drug abuse. The methodology used in the article, which discusses the guarantee of protection given to whistleblowers regarding the provision of information about drug abuse, uses normative legal research, using a statutory legal approach in analyzing the legal issues discussed. In the end, specifically, Drug abuse is regulated in the Narcotics Law. Drug abuse is also regulated by other regulations, namely Supreme Court Circular No. 4 of 2010. However, the Supreme Court Circular only regulates the